Translation Theory -- A Gateway to Comprehending Culture - Antunović, Goranka (Array, 2006)
In view of the common description of translation / interpreting as ‘ bridging gaps between (members of) different cultures’ , it is only logical to deem multiple cultural competence a conspicuous element of the overall translator’ s competence and, consequently, an essential element in translator training. However, neither ‘ culture’ nor ‘ intercultural transfer’ is normally granted a comprehensive approach within one single course. Typically, culture-related issues surface in practical translation classes and, possibly, in a course devoted to the culture associated with the student’ s foreign language. The author suggests that such a situation – typical of Croatia today and probably after the university reform as well – urges that ‘ culture’ be highlighted within the course on translation theory. ‘ Culture’ should figure in discussion of various conspicuous topics of translation theory, namely the translation process and its elements, the concept of equivalence, the choice of translation strategy etc. The author shall share some ideas as to how that can be done by presenting her model of the translation process in which culture(s) figure(s) as the backdrop to all the other elements (languages, texts, situations, participants). It thus exerts a paramount influence on the selection of the general translation strategy and of individual translation equivalents. The points will be illustrated by examples established by the author in translations involving three languages and cultures: Croatian, English and Swedish. G. Toury’ s discussion and classification of translation norms (Toury 1995) shall be highlighted as a useful framework in discussing the cultural setting of translation.